AKIBAT HUKUM PERJANJIAN PELEPASAN HAK DI BAWAH TANGAN SEBAGAI UPAYA MEMPEROLEH TANAH OBYEK SENGKETA DALAM PUTUSAN PENGADILAN NEGERI JAKARTA TIMUR NOMOR 133/PDT.G/2018/PN.JKT.TIM - Jimmy Gunawan; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2020)
Land disputes are disputes over ownership or control between individuals, legal entities or institutions that do not have broad socio-political impacts. Buying and selling land must be done in a clear and cash. The problem faced in writing this thesis is how the legal consequences of the relinquishment of rights privately made as an effort to acquire land objects of dispute in the East Jakarta District Court Decision Number 133/Pdt.G/2018/PN.Jkt.Tim. The research method used in writing this thesis is normative legal research. The results of the study show that land rights have been transferred from the Seller to the Buyer, because Indonesia's national agrarian law adheres to customary law, in which the nature of buying and selling is clear and cash. On the other hand, the legal consequence is that it does not cause the disputed land to be acquired or owned by a third party named Jenny Tsin. Acquisition of land with a relinquishment of rights, relinquishment of rights must be carried out first through the land agency and then must be followed by a new application for rights in accordance with the allocation. Where there are rulesor procedures that must be followed, namely the relinquishment of rights must be carried out through a land institution, and there is a new application for rights, and then the land can be acquired / owned by the person who needs the land.